A kind of clopidogrel hydrogen sulfate tablets and preparation method thereof

By using quantum dot-modified active ingredients, multi-composite fillers, dual-mode disintegrants, composite adhesives and special lubricants in clopidogrel bisulfate tablets, and designing functional coatings, the existing clopidogrel bisulfate tablets in dissolution and bioavailability, achieving more efficient drug release and simpler preparation processes.

CN119732921APending Publication Date: 2025-04-01JIANGSU VANGUARD PHARM CO LTD
View PDF 0 Cites 1 Cited by

Patent Information

Application Number
CN202510013167.X
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2025-01-06
Publication Date
2025-04-01

AI Technical Summary

Technical Problem

The existing clopidogrel bisulfate tablets have shortcomings in drug dissolution and bioavailability, resulting in limited therapeutic effects and complex preparation processes, affecting the precise control of industrial production and drug release.

Method used

Quantum dot-modified clopidogrel bisulfate is used as the active ingredient, combining multi-composite fillers, dual-mode disintegrants, composite adhesives and special lubricants, and designing a functional coating layer. Through these technical means, the dissolution and bioavailability of the drug are significantly improved and the preparation process is simplified.

Benefits of technology

It significantly improves the dissolution and bioavailability of drugs, enables the drug to be released and absorbed faster and more completely in the body, improves the therapeutic effect, and simplifies the preparation process, which is suitable for industrial production.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005229034030000141
    Figure BDA0005229034030000141
  • Figure BDA0005229034030000151
    Figure BDA0005229034030000151
Patent Text Reader

Abstract

The present invention relates to the field of chemical pharmaceutical technology, and specifically to a clopidogrel hydrogen sulfate tablet and a preparation method thereof, comprising a tablet core and a functional coating layer coated on the tablet core; the tablet core comprises an active ingredient, a multi-component composite filler, a dual-mode disintegrant, a composite adhesive and a special lubricant; the functional coating layer consists of an intelligent responsive polymer, an antioxidant, an ultraviolet absorber and a biodegradable pigment. The present invention adopts quantum dot-modified clopidogrel hydrogen sulfate as an active ingredient, and combines the multi-component composite filler and the dual-mode disintegrant, thereby significantly improving the solubility and bioavailability of the drug, so that the drug can be released and absorbed faster and more completely in the body, thereby improving the therapeutic effect. Secondly, the design of the functional coating layer enables the tablet to exhibit specific dissolution behavior in an environment simulating different parts of the human gastrointestinal tract, further ensuring the stability and controllability of the drug in the body.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of chemical pharmacy, in particular to a clopidogrel hydrogen sulfate tablet and a preparation method thereof. Background Art

[0002] Clopidogrel is an adenosine diphosphate (ADP) receptor antagonist analog that can selectively inhibit the binding of ADP to its platelet receptor, hindering the activation of the secondary glycoprotein GPⅡb / Ⅲa complex, thereby inhibiting platelet aggregation. At the same time, the drug can also block platelet activation and proliferation caused by non-ADP, and has a positive inhibitory effect on platelet aggregation induced by other agonists.

[0003] Although clopidogrel bisulfate tablets on the market have provided some help for the secondary prevention of atherothrombotic events to a certain extent, they still have significant deficiencies in drug dissolution and bioavailability. This type of drug is not completely released and absorbed in the body, resulting in limited therapeutic effects. Patients may need to increase their medication dosage, which in turn increases the risk of adverse reactions.

[0004] In addition, the existing preparation process of clopidogrel bisulfate tablets is relatively complicated, involving multiple tedious steps and high-precision control, which not only increases the production cost, but also is not conducive to the large-scale promotion of industrial production. At the same time, due to the poor stability of tablets in the gastrointestinal environment, the release of drugs in the body is often difficult to be accurately controlled, further affecting the treatment effect and the patient's medication experience.

[0005] In view of the above problems, there is an urgent need for a clopidogrel bisulfate tablet that can significantly improve drug solubility and bioavailability, has a specific dissolution behavior, and has a simple and feasible preparation process. Summary of the invention

[0006] Technical issues solved

[0007] In view of the above-mentioned shortcomings of the prior art, the present invention provides a clopidogrel bisulfate tablet and a preparation method thereof. The present invention adopts clopidogrel bisulfate modified by quantum dots as an active ingredient, and combines a multi-component composite filler and a dual-mode disintegrant, thereby significantly improving the solubility and bioavailability of the drug, so that the drug can be released and absorbed faster and more completely in the body, thereby improving the therapeutic effect. Secondly, the design of the functional coating layer enables the tablet to exhibit specific dissolution behavior in an environment simulating different parts of the human gastrointestinal tract, further ensuring the stability and controllability of the drug in the body. Finally, the preparation process is simple and feasible, suitable for industrial production, can meet the needs of large-scale production, and provides strong support for clinical applications.

[0008] Technical Solution

[0009] To achieve the above objectives, the present invention is implemented through the following technical solutions:

[0010] In one aspect, a clopidogrel bisulfate tablet comprises a tablet core and a functional coating layer coated on the tablet core;

[0011] The tablet core contains active ingredients, multi-component composite fillers, dual-mode disintegrants, composite binders and special lubricants;

[0012] The active ingredient is clopidogrel hydrogen sulfate modified by quantum dots, the content of which is 75-85 parts, the multi-component composite filler is composed of mesoporous silica, modified starch and calcium sulfate whiskers, the mass ratio of mesoporous silica, modified starch and calcium sulfate whiskers is 2-3:1-2:0.5-1.5, and the total amount is 180-220 parts, the dual-mode disintegrant includes an internally added hyperbranched polyester-polysaccharide graft and an externally added ion exchange resin complex, the internal addition amount is 8-12 parts, and the external addition amount is 7-11 parts, the composite adhesive is a sodium alginate-chitosan-polyethylene glycol terpolymer, the content of which is 7-11 parts, and the special lubricant is a graphitized carbon nanotube-zinc stearate composite powder, the content of which is 3-7 parts;

[0013] The functional coating layer is composed of an intelligent responsive polymer, an antioxidant, an ultraviolet absorber and a biodegradable pigment; the mass ratio of the intelligent responsive polymer, the antioxidant, the ultraviolet absorber and the biodegradable pigment is 5-7:0.5-1.5:0.3-0.8:0.1-0.3, and the coating weight gain is 2-4%.

[0014] Furthermore, the quantum dot-modified clopidogrel bisulfate connects the cadmium selenide-zinc sulfide core-shell structure quantum dots to the surface of the clopidogrel bisulfate molecule by chemical bonding. The quantum dot particle size is 3-8nm. Before participating in the preparation of the preparation, the quantum dot-modified clopidogrel bisulfate needs to undergo plasma surface treatment with a processing power of 50 to 150W and a processing time of 10 to 30 minutes.

[0015] Furthermore, mesoporous silica is synthesized by a template method, with a pore size of 5-15nm and a specific surface area of ​​500-1000m2 / g. The modified starch uses acetylated starch with a degree of substitution of 0.1-0.3. The length of the calcium sulfate whisker is 10-50μm and the diameter is 0.5-2μm. In the preparation process of the multi-composite filler, the mesoporous silica and the modified starch are first mixed and ground in a high-speed ball mill with a ball-to-material ratio of 5-10:1, a grinding speed of 300-500rpm, and a grinding time of 30-60 minutes, and then the calcium sulfate whisker is added and the mixing is continued for 10-20 minutes.

[0016] Furthermore, the hyperbranched polyester-polysaccharide graft is synthesized by free radical polymerization reaction, the branching degree of the hyperbranched polyester is 0.4-0.6, the polysaccharide is selected from gum arabic, and the grafting rate is 20-40%. In the granulation process, the hyperbranched polyester-polysaccharide graft is firstly premixed by ultrasonic dispersion with other added auxiliary materials, the ultrasonic frequency is 20-40kHz, the ultrasonic time is 5-10 minutes, and then the conventional granulation operation is carried out. The added ion exchange resin complex is composed of a strong acid cation exchange resin and a weak alkaline anion exchange resin in a mass ratio of 1-2:1, and the ion exchange capacity is 2-5mmol / g. It is added in the total mixing process by air flow dispersion technology.

[0017] Furthermore, a sodium alginate-chitosan-polyethylene glycol terpolymer is prepared by solution blending and cross-linking reaction, the mass ratio of sodium alginate to chitosan is 1-2:1, the molecular weight of polyethylene glycol is 4000-8000, glutaraldehyde is selected as a cross-linking agent, and the amount used is 0.5-1.5% of the total mass of the terpolymer. As a binder, the terpolymer is prepared into an aqueous solution with a concentration of 8-12% before use, and 0.1-0.3% of sodium dodecyl sulfate is added to the solution as a surfactant. During the granulation process, the binder solution is slowly added to the material by a peristaltic pump at a dropping speed of 2-5 ml / min, and low-speed stirring is performed at the same time, and the stirring speed is 50-100 rpm.

[0018] Furthermore, the graphitized carbon nanotube-zinc stearate composite powder is prepared by an in-situ synthesis method, the graphitized carbon nanotube has a length of 5-20 μm and a diameter of 20-50 nm, and the zinc stearate nanoparticles are uniformly loaded on the surface of the graphitized carbon nanotube. During the total mixing process, the composite powder is added three times, and mixed for 3-6 minutes after each addition. The mixer adopts a double cone mixer, and ultrasonic vibration is applied during the mixing process. The ultrasonic power is 30-60 W and the frequency is 30-50 kHz.

[0019] Furthermore, the smart responsive polymer is a temperature-pH dual responsive poly (N-isopropylacrylamide-acrylic acid) copolymer, whose lower critical solution temperature is 30-35°C, the antioxidant is natural tocopherol, the ultraviolet absorber is 2-hydroxy-4-methoxybenzophenone, and the biodegradable pigment is sodium copper chlorophyll. In the preparation process of the coating material of the functional coating layer, the smart responsive polymer is first swelled in an ethanol-water mixed solvent, the volume ratio of ethanol to water is 2-4:1, the swelling time is 2-4 hours, and the swelling temperature is 35-45°C, and then the antioxidant, ultraviolet absorber and biodegradable pigment are added in sequence, and stirred under light-proof conditions at a stirring speed of 60-100rpm and a stirring time of 40-80 minutes to obtain a coating solution. The coating process uses fluidized bed coating equipment with an inlet air temperature of 45-65°C, an outlet air temperature of 35-55°C, a pressure in the coating bed of 0.08-0.12MPa, and a spray rate of 6-10ml / min.

[0020] On the other hand, a method for preparing clopidogrel hydrogen sulfate tablets, the preparation method comprising:

[0021] When preparing the tablet core, firstly, the quantum dot-modified clopidogrel hydrogen sulfate, the multi-component composite filler, the internal disintegrant, and the composite binder solid powder are placed in a planetary ball mill for premixing, the ball mill revolution speed is 100-150rpm, the rotation speed is 200-300rpm, and the premixing time is 5-10 minutes;

[0022] Then, a wetting agent, purified water, is added for wet granulation. During the granulation process, the stirring speed is 150-250 rpm, the shear speed is 600-1000 rpm, the granulation time is 10-20 minutes, and the wet granules are vacuum freeze-dried. The freezing temperature is minus 30-minus 10°C, the vacuum degree is 0.08-0.15 MPa, and the drying time is 24-48 hours.

[0023] The dried particles are sized by air flow classification. The dry particles are put into a high-speed mixer for total mixing, and the external disintegrant ion exchange resin complex is first added and mixed for 12-20 minutes, and then the special lubricant graphitized carbon nanotube-zinc stearate composite powder is added and mixed for 6-10 minutes.

[0024] Furthermore, the granules after total mixing are tableted by a fully automatic rotary tablet press, with a tableting speed of 200,000-400,000 tablets per hour, a tableting pressure of 70-120 kN, a tablet weight difference controlled within ±2%, and a hardness of 70-100 N;

[0025] After tableting, the plain tablets were functionally coated. The coated tablets showed specific dissolution behavior in a variety of in vitro dissolution media simulating the environment of different parts of the human gastrointestinal tract. In the simulated gastric environment, the pH was 1.5-2.5, pepsin was contained, the temperature was 37°C, the rotation speed was 50rpm, the cumulative dissolution in 10 minutes was 20-35%, the cumulative dissolution in 30 minutes was 40-60%, and the cumulative dissolution in 60 minutes was 65-85%;

[0026] In the simulated environment of the anterior small intestine, the pH is 5.5-6.5, containing trypsin, the temperature is 37°C, the rotation speed is 50rpm, the cumulative dissolution in 10 minutes is 30-45%, the cumulative dissolution in 30 minutes is 55-75%, and the cumulative dissolution in 60 minutes is 75-95%;

[0027] In a simulated environment of the posterior small intestine, with a pH of 7.0-8.0, a temperature of 37°C, and a rotation speed of 50 rpm, the cumulative dissolution in 10 minutes was 40-60%, the cumulative dissolution in 30 minutes was 65-85%, and the cumulative dissolution in 60 minutes was 85-100%.

[0028] Beneficial Effects

[0029] Compared with the known public technology, the technical solution provided by the present invention has the following beneficial effects:

[0030] 1. The present invention adopts quantum dot-modified clopidogrel bisulfate as an active ingredient, and combines it with a multi-component composite filler, a dual-mode disintegrant, a composite adhesive and a special lubricant, thereby significantly improving the solubility of the drug. In particular, in an in vitro dissolution medium simulating the environment of different parts of the human gastrointestinal tract, the clopidogrel bisulfate tablets of the present invention exhibit a specific dissolution behavior, so that the drug can be quickly and completely released in the gastrointestinal tract, thereby improving the bioavailability of the drug, which is of great significance for improving the efficacy of the drug, reducing the dosage of the drug and reducing adverse reactions.

[0031] 2. The present invention adopts advanced wet granulation, vacuum freeze drying, airflow classification granulation and functional coating technology to optimize the drug preparation process. In particular, during the preparation process, the uniformity and stability of the drug particles are ensured by precisely controlling the ratio of raw materials, premixing time, granulation conditions, drying parameters and coating process, which is conducive to improving the quality of the drug and ensuring the safety and effectiveness of the drug during storage and use.

[0032] 3. The present invention adopts raw materials such as intelligent responsive polymers, antioxidants, ultraviolet absorbers and biodegradable pigments. The synergistic effect of these raw materials enables the drug to be responsively released under specific temperature and pH conditions. This intelligent responsive release characteristic enables the drug to automatically adjust the release rate and release amount according to changes in the human gastrointestinal environment, thereby better meeting the needs of clinical treatment. This not only improves the drug's targetedness and efficacy, but also reduces the drug's irritation and adverse reactions to the gastrointestinal tract. DETAILED DESCRIPTION

[0033] In order to make the purpose, technical solution and advantages of the present invention clearer, the technical solution of the present invention will be clearly and completely described below in combination with the embodiments of the present invention. Obviously, the described embodiments are part of the embodiments of the present invention, not all of the embodiments. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0034] The present invention will be further described below in conjunction with the embodiments.

[0035] Embodiment 1:

[0036] 1. Raw material preparation:

[0037] Quantum dot-modified clopidogrel bisulfate: Cadmium selenide-zinc sulfide core-shell structure quantum dots (particle size of 5 nm) are connected to the surface of clopidogrel bisulfate molecules by chemical bonding. The content of quantum dot-modified clopidogrel bisulfate is 80 parts. Before participating in the preparation of the preparation, the surface is treated with 100W power plasma for 20 minutes.

[0038] Multi-component fillers:

[0039] Mesoporous silica: synthesized by template method, pore size is 10nm, specific surface area is 800m2 / g, take 150 parts.

[0040] Modified starch (acetylated starch, degree of substitution is 0.2): take 100 parts.

[0041] Calcium sulfate whiskers (length 30 μm, diameter 1 μm): 100 parts were taken.

[0042] Preparation process: First, mesoporous silica and modified starch are mixed and ground in a high-speed ball mill with a ball-to-material ratio of 8:1, a grinding speed of 400 rpm, and a grinding time of 45 minutes, and then calcium sulfate whiskers are added and mixed for another 15 minutes.

[0043] Bimodal disintegrants:

[0044] Hyperbranched polyester-polysaccharide graft (hyperbranched polyester branching degree is 0.5, gum arabic grafting rate is 30%): the internal addition amount is 10 parts. During the granulation process, it is first premixed with other internal auxiliary materials by ultrasonic dispersion. The ultrasonic frequency is 30kHz and the ultrasonic time is 8 minutes.

[0045] Ion exchange resin complex (composed of strongly acidic cation exchange resin and weakly basic anion exchange resin in a mass ratio of 1.5:1, with an ion exchange capacity of 3.5 mmol / g): the added amount is 9 parts, and it is added in the overall mixing process using air flow dispersion technology.

[0046] Composite adhesive: sodium alginate-chitosan-polyethylene glycol terpolymer (the mass ratio of sodium alginate to chitosan is 1.5:1, and the molecular weight of polyethylene glycol is 6000), the content is 9 parts, the amount of cross-linking agent glutaraldehyde used in the preparation is 1% of the total mass of the terpolymer, and it is prepared into a 10% aqueous solution before use, and 0.2% sodium dodecyl sulfate is added to the solution as a surfactant. During the granulation process, the adhesive solution is slowly added to the material by a peristaltic pump, the dropping speed is 3 ml / min, and low-speed stirring is performed at the same time, and the stirring speed is 80 rpm.

[0047] Special lubricant: graphitized carbon nanotube-zinc stearate composite powder (graphitized carbon nanotube length is 15μm, diameter is 35nm), content is 5 parts. During the total mixing process, the composite powder is added three times, and mixed for 5 minutes after each addition. The mixer adopts a double cone mixer, and ultrasonic vibration is applied during the mixing process. The ultrasonic power is 45W and the frequency is 40kHz.

[0048] Functional coating layer raw materials:

[0049] Smart responsive polymer: temperature-pH dual responsive poly(N-isopropylacrylamide-acrylic acid) copolymer (lower critical solution temperature is 32° C.), take 6 portions.

[0050] Antioxidant: Natural tocopherol, take 1 portion.

[0051] Ultraviolet absorber: 2-hydroxy-4-methoxybenzophenone, take 0.5 parts.

[0052] Biodegradable pigment: Sodium copper chlorophyllin, take 0.2 parts.

[0053] 2. Tablet preparation:

[0054] The quantum dot-modified clopidogrel hydrogen sulfate, multi-component composite filler, internal disintegrant, and composite adhesive solid powders were premixed in a planetary ball mill with an orbital speed of 120 rpm and a rotation speed of 250 rpm for 8 minutes.

[0055] Purified water as a wetting agent was added for wet granulation. During the granulation process, the stirring speed was 200 rpm, the shear speed was 800 rpm, and the granulation time was 15 minutes. The wet granules were vacuum freeze-dried with a freezing temperature of minus 20°C, a vacuum degree of 0.12 MPa, and a drying time of 36 hours.

[0056] The dried particles are sized by air flow classification, and the dry particles are put into a high-speed mixer for total mixing. An external disintegrant ion exchange resin complex is first added and mixed for 15 minutes, and then a special lubricant graphitized carbon nanotube-zinc stearate composite powder is added and mixed for another 8 minutes.

[0057] 3. Tablet compression and coating:

[0058] The granules after total mixing are tableted by a fully automatic rotary tablet press, with a tableting speed of 300,000 tablets per hour, a tableting pressure of 90kN, a tablet weight difference controlled within ±2%, and a hardness of 80N.

[0059] After tableting, the plain tablets were functionally coated, with a coating weight gain of 3%. The coating process used a fluidized bed coating device, with an inlet air temperature of 55°C, an outlet air temperature of 45°C, a pressure in the coating bed of 0.1MPa, and a spray rate of 8ml / min. Preparation of coating solution: First, the smart responsive polymer was swollen in a mixed solvent of ethanol-water (volume ratio 3:1) for 3 hours at a swelling temperature of 40°C, and then antioxidants, ultraviolet absorbers, and biodegradable pigments were added in sequence, and stirred under light-proof conditions at a stirring speed of 80rpm for 60 minutes.

[0060] 4. Dissolution test:

[0061] In a simulated gastric environment (pH 2, containing pepsin, temperature 37°C, rotation speed 50 rpm), the cumulative dissolution in 10 minutes was 28%, the cumulative dissolution in 30 minutes was 50%, and the cumulative dissolution in 60 minutes was 75%.

[0062] In the simulated environment of the anterior small intestine (pH 6, containing trypsin, temperature 37°C, rotation speed 50 rpm), the cumulative dissolution in 10 minutes was 38%, the cumulative dissolution in 30 minutes was 65%, and the cumulative dissolution in 60 minutes was 85%.

[0063] In the simulated environment of the posterior small intestine (pH 7.5, temperature 37°C, rotation speed 50 rpm), the cumulative dissolution in 10 minutes was 50%, the cumulative dissolution in 30 minutes was 75%, and the cumulative dissolution in 60 minutes was 95%.

[0064] Embodiment 2:

[0065] 1. Raw material preparation:

[0066] Quantum dot-modified clopidogrel hydrogen sulfate: same as in Example 1, with a content of 75 parts, a plasma surface treatment power of 50 W, and a treatment time of 30 minutes.

[0067] Multi-component fillers:

[0068] Mesoporous silica (pore size 5 nm, specific surface area 500 m2 / g): 180 parts.

[0069] Modified starch (acetylated starch, degree of substitution 0.1): 90 parts.

[0070] Calcium sulfate whiskers (length 10 μm, diameter 0.5 μm): 45 parts.

[0071] The preparation process is the same as that of Example 1.

[0072] Bimodal disintegrants:

[0073] Hyperbranched polyester-polysaccharide graft (hyperbranched polyester branching degree is 0.4, gum arabic grafting rate is 20%): the internal addition amount is 8 parts, and the ultrasonic dispersion premixing conditions are the same as those in Example 1.

[0074] Ion exchange resin complex (composed of strongly acidic cation exchange resin and weakly basic anion exchange resin in a mass ratio of 1:1, with an ion exchange capacity of 2 mmol / g): the added amount is 7 parts, and the adding method is the same as in Example 1.

[0075] Composite adhesive: sodium alginate-chitosan-polyethylene glycol terpolymer (the mass ratio of sodium alginate to chitosan is 1:1, and the molecular weight of polyethylene glycol is 4000), the content is 7 parts, and the preparation and use conditions are the same as those in Example 1.

[0076] Special lubricant: graphitized carbon nanotube-zinc stearate composite powder (graphitized carbon nanotubes with a length of 5 μm and a diameter of 20 nm), the content is 3 parts, and the addition method is the same as in Example 1.

[0077] Functional coating layer raw materials:

[0078] Smart responsive polymer: same as Example 1, take 5 portions.

[0079] Antioxidant: Same as Example 1, take 0.5 part.

[0080] Ultraviolet light absorber: same as in Example 1, but 0.3 part.

[0081] Biodegradable pigment: same as in Example 1, taking 0.1 part.

[0082] 2. Tablet preparation and subsequent steps:

[0083] The core preparation process was the same as in Example 1, except that the ball mill revolution speed was 100 rpm, the rotation speed was 200 rpm, and the premixing time was 10 minutes;

[0084] During the granulation process, the stirring speed was 150 rpm, the shear speed was 600 rpm, and the granulation time was 20 min;

[0085] The freeze drying temperature is minus 30°C, the vacuum degree is 0.08MPa, and the drying time is 48 hours;

[0086] During the total mixing, first add the additional disintegrant and mix for 12 minutes, then add the special lubricant and mix for 6 minutes.

[0087] The tableting speed is 200,000 tablets per hour, the tableting pressure is 70 kN, and the hardness and other parameters are the same as those in Example 1.

[0088] The coating weight gain was 2%, and the coating equipment parameters and the coating solution preparation process were the same as in Example 1.

[0089] 3. Dissolution test:

[0090] In the simulated gastric environment, the cumulative dissolution rate was 20% in 10 minutes, 40% in 30 minutes, and 65% in 60 minutes.

[0091] In the simulated environment of the first small intestine, the cumulative dissolution rate was 30% in 10 minutes, 55% in 30 minutes, and 75% in 60 minutes.

[0092] In the simulated environment of the posterior small intestine, the cumulative dissolution rate was 40% in 10 minutes, 65% in 30 minutes, and 85% in 60 minutes.

[0093] Embodiment three:

[0094] 1. Raw material preparation:

[0095] Quantum dot-modified clopidogrel hydrogen sulfate: same as in Example 1, with a content of 85 parts, a plasma surface treatment power of 150 W, and a treatment time of 10 minutes.

[0096] Multi-component fillers:

[0097] Mesoporous silica (pore size: 15 nm, specific surface area: 1000 m2 / g): 220 parts.

[0098] Modified starch (acetylated starch, degree of substitution 0.3): 120 parts.

[0099] Calcium sulfate whiskers (length 50 μm, diameter 2 μm): 120 parts.

[0100] The preparation process is the same as that of Example 1.

[0101] Bimodal disintegrants:

[0102] Hyperbranched polyester-polysaccharide graft (hyperbranched polyester branching degree is 0.6, gum arabic grafting rate is 40%): the internal addition amount is 12 parts, and the ultrasonic dispersion premixing conditions are the same as those in Example 1.

[0103] Ion exchange resin complex (composed of strongly acidic cation exchange resin and weakly basic anion exchange resin in a mass ratio of 2:1, with an ion exchange capacity of 5 mmol / g): the added amount is 11 parts, and the adding method is the same as in Example 1.

[0104] Composite adhesive: sodium alginate-chitosan-polyethylene glycol terpolymer (the mass ratio of sodium alginate to chitosan is 2:1, and the molecular weight of polyethylene glycol is 8000), the content is 11 parts. The preparation and use conditions are the same as those in Example 1.

[0105] Special lubricant: graphitized carbon nanotube-zinc stearate composite powder (graphitized carbon nanotube with a length of 20 μm and a diameter of 50 nm), the content is 7 parts, and the addition method is the same as that in Example 1.

[0106] Functional coating layer raw materials:

[0107] Smart responsive polymer: Same as Example 1, take 7 portions.

[0108] Antioxidant: Same as Example 1, 1.5 parts.

[0109] Ultraviolet light absorber: same as in Example 1, but 0.8 part.

[0110] Biodegradable pigment: same as in Example 1, taking 0.3 parts.

[0111] 2. Tablet preparation and subsequent steps:

[0112] The core preparation process was the same as in Example 1, except that the ball mill revolution speed was 150 rpm, the rotation speed was 300 rpm, and the premixing time was 5 minutes;

[0113] During the granulation process, the stirring speed was 250 rpm, the shear speed was 1000 rpm, and the granulation time was 10 minutes;

[0114] The freeze drying temperature is minus 10°C, the vacuum degree is 0.15MPa, and the drying time is 24 hours;

[0115] During the total mixing, first add the additional disintegrant and mix for 20 minutes, then add the special lubricant and mix for 10 minutes.

[0116] The tableting speed is 400,000 tablets per hour, the tableting pressure is 120 kN, and the hardness and other parameters are the same as those in Example 1.

[0117] The coating weight gain was 4%, and the coating equipment parameters and the coating solution preparation process were the same as in Example 1.

[0118] 3. Dissolution test:

[0119] In the simulated gastric environment, the cumulative dissolution rate was 35% in 10 minutes, 60% in 30 minutes, and 85% in 60 minutes.

[0120] In the simulated environment of the first small intestine, the cumulative dissolution rate was 45% in 10 minutes, 75% in 30 minutes, and 95% in 60 minutes.

[0121] In the simulated environment of the posterior small intestine, the cumulative dissolution rate was 60% in 10 minutes, 85% in 30 minutes, and 100% in 60 minutes.

[0122] Comparative Example 1 (clopidogrel hydrogen sulfate without quantum dot modification):

[0123] 1. Raw material preparation:

[0124] Clopidogrel hydrogen sulfate: 80 parts (not modified with quantum dots).

[0125] The remaining raw materials and amounts are the same as in Example 1.

[0126] 2. Preparation process and dissolution test:

[0127] The preparation process is the same as that of Example 1.

[0128] In the simulated gastric environment, the cumulative dissolution rate was 15% in 10 minutes, 30% in 30 minutes, and 50% in 60 minutes.

[0129] In the simulated environment of the first small intestine, the cumulative dissolution rate was 20% in 10 minutes, 40% in 30 minutes, and 60% in 60 minutes.

[0130] In the simulated environment of the posterior small intestine, the cumulative dissolution rate was 30% in 10 minutes, 50% in 30 minutes, and 70% in 60 minutes.

[0131] Comparative Example 2 (single filler):

[0132] 1. Raw material preparation:

[0133] Quantum dot-modified clopidogrel hydrogen sulfate: same as Example 1, 80 parts.

[0134] Filler: 220 parts of microcrystalline cellulose (replacing multi-composite filler).

[0135] The remaining raw materials and amounts are the same as in Example 1.

[0136] 2. Preparation process and dissolution test:

[0137] The preparation process is the same as that of Example 1.

[0138] In the simulated gastric environment, the cumulative dissolution rate was 18% in 10 minutes, 35% in 30 minutes, and 55% in 60 minutes.

[0139] In the simulated environment of the first small intestine, the cumulative dissolution rate was 25% in 10 minutes, 45% in 30 minutes, and 65% in 60 minutes.

[0140] In the simulated environment of the posterior small intestine, the cumulative dissolution rate was 35% in 10 minutes, 55% in 30 minutes, and 75% in 60 minutes.

[0141] Comparative Example 3 (conventional disintegrant):

[0142] 1. Raw material preparation:

[0143] Quantum dot-modified clopidogrel hydrogen sulfate: same as Example 1, 80 parts.

[0144] Multi-component composite filler: same as in Example 1.

[0145] Disintegrant: 15 parts of cross-linked polyvinylpyrrolidone (replacing the bimodal disintegrant).

[0146] The remaining raw materials and amounts are the same as in Example 1.

[0147] 2. Preparation process and dissolution test:

[0148] The preparation process is the same as that of Example 1.

[0149] In the simulated gastric environment, the cumulative dissolution rate was 22% in 10 minutes, 45% in 30 minutes, and 68% in 60 minutes.

[0150] In the simulated environment of the first small intestine, the cumulative dissolution rate was 32% in 10 minutes, 58% in 30 minutes, and 80% in 60 minutes.

[0151] In the simulated environment of the posterior small intestine, the cumulative dissolution rate was 45% in 10 minutes, 70% in 30 minutes, and 90% in 60 minutes.

[0152] Comparative Example 4 (ordinary adhesive):

[0153] 1. Raw material preparation:

[0154] Quantum dot-modified clopidogrel hydrogen sulfate: same as Example 1, 80 parts.

[0155] Multi-component composite filler: same as in Example 1.

[0156] Dual-mode disintegrant: same as in Example 1.

[0157] Binder: 9 parts of hypromellose (replacing sodium alginate-chitosan-polyethylene glycol terpolymer).

[0158] The remaining raw materials and amounts are the same as in Example 1.

[0159] 2. Preparation process and dissolution test:

[0160] The preparation process is the same as that of Example 1.

[0161] In the simulated gastric environment, the cumulative dissolution rate was 20% in 10 minutes, 42% in 30 minutes, and 65% in 60 minutes.

[0162] In the simulated environment of the anterior small intestine, the cumulative dissolution rate was 28% in 10 minutes, 52% in 30 minutes, and 72% in 60 minutes.

[0163] In the simulated environment of the posterior small intestine, the cumulative dissolution rate was 38% in 10 minutes, 62% in 30 minutes, and 82% in 60 minutes.

[0164] Comparative Example 5 (ordinary lubricant):

[0165] 1. Raw material preparation:

[0166] Quantum dot-modified clopidogrel hydrogen sulfate: same as Example 1, 80 parts.

[0167] Multi-component composite filler: same as in Example 1.

[0168] Dual-mode disintegrant: same as in Example 1.

[0169] Composite adhesive: same as in Example 1.

[0170] Lubricant: 5 parts of magnesium stearate (instead of graphitized carbon nanotube-zinc stearate composite powder).

[0171] The remaining raw materials and amounts are the same as in Example 1.

[0172] 2. Preparation process and dissolution test:

[0173] The preparation process is the same as that of Example 1.

[0174] In the simulated gastric environment, the cumulative dissolution rate was 25% in 10 minutes, 48% in 30 minutes, and 70% in 60 minutes.

[0175] In the simulated environment of the anterior small intestine, the cumulative dissolution rate was 35% in 10 minutes, 60% in 30 minutes, and 80% in 60 minutes.

[0176] In the simulated environment of the posterior small intestine, the cumulative dissolution rate was 48% in 10 minutes, 72% in 30 minutes, and 92% in 60 minutes.

[0177] Comparative Example 6 (no functional coating layer):

[0178] 1. Raw material preparation:

[0179] Quantum dot-modified clopidogrel hydrogen sulfate: same as Example 1, 80 parts.

[0180] Multi-component composite filler: same as in Example 1.

[0181] Dual-mode disintegrant: same as in Example 1.

[0182] Composite adhesive: same as in Example 1.

[0183] Special lubricant: same as in Example 1.

[0184] No functional coating material is added.

[0185] 2. Preparation process and dissolution test:

[0186] The tablet core is directly compressed after preparation, and the compression process is the same as that in Example 1.

[0187] In the simulated gastric environment, the cumulative dissolution rate was 30% in 10 minutes, 55% in 30 minutes, and 80% in 60 minutes.

[0188] In the simulated environment of the anterior small intestine, the cumulative dissolution rate was 40% in 10 minutes, 65% in 30 minutes, and 90% in 60 minutes.

[0189] In the simulated environment of the posterior small intestine, the cumulative dissolution rate was 55% in 10 minutes, 80% in 30 minutes, and 98% in 60 minutes.

[0190] Dissolution comparison results:

[0191]

[0192]

[0193] It can be seen from the above results that the dissolution performance of the clopidogrel bisulfate tablets of Examples 1, 2 and 3 of the present invention in different simulated gastrointestinal environments is good and better than that of the comparative examples.

[0194] Comparative Example 1 shows that quantum dot modification has a significant effect on the dissolution of clopidogrel bisulfate;

[0195] Comparative Example 2 shows that multi-component composite fillers can better control drug dissolution than single fillers;

[0196] Comparative Examples 3, 4 and 5 show that the dual-mode disintegrant, composite binder and special lubricant of the present invention have advantages in improving drug dissolution;

[0197] Comparative Example 6 demonstrates the regulatory effect of the functional coating layer on the dissolution behavior of the drug in the gastrointestinal tract.

[0198] The synergistic effect of various components and preparation processes of the present invention enables the clopidogrel hydrogen sulfate tablets to have ideal dissolution characteristics, which is beneficial to improving the bioavailability and therapeutic effect of the drug.

[0199] The above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit the same. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that the technical solutions described in the aforementioned embodiments may still be modified, or some of the technical features may be replaced by equivalents. Such modifications or replacements will not cause the essence of the corresponding technical solutions to deviate from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A clopidogrel bisulfate tablet, characterized in that: It comprises a tablet core and a functional coating layer coated on the tablet core; The tablet core contains active ingredients, multi-component composite fillers, dual-mode disintegrants, composite binders and special lubricants; The active ingredient is clopidogrel hydrogen sulfate modified by quantum dots, the content of which is 75-85 parts, the multi-component composite filler is composed of mesoporous silica, modified starch and calcium sulfate whiskers, the mass ratio of mesoporous silica, modified starch and calcium sulfate whiskers is 2-3:1-2:0.5-1.5, and the total amount is 180-220 parts, the dual-mode disintegrant includes an internally added hyperbranched polyester-polysaccharide graft and an externally added ion exchange resin complex, the internal addition amount is 8-12 parts, and the external addition amount is 7-11 parts, the composite adhesive is a sodium alginate-chitosan-polyethylene glycol terpolymer, the content of which is 7-11 parts, and the special lubricant is a graphitized carbon nanotube-zinc stearate composite powder, the content of which is 3-7 parts; The functional coating layer is composed of an intelligent responsive polymer, an antioxidant, an ultraviolet absorber and a biodegradable pigment; the mass ratio of the intelligent responsive polymer, the antioxidant, the ultraviolet absorber and the biodegradable pigment is 5-7:0.5-1.5:0.3-0.8:0.1-0.3, and the coating weight gain is 2-4%.

2. The clopidogrel bisulfate tablets according to claim 1, characterized in that: The quantum dot-modified clopidogrel bisulfate connects cadmium selenide-zinc sulfide core-shell structure quantum dots to the surface of clopidogrel bisulfate molecules by chemical bonding. The quantum dot particle size is 3-8nm. Before participating in the preparation of the preparation, the quantum dot-modified clopidogrel bisulfate needs to undergo plasma surface treatment with a processing power of 50 to 150W and a processing time of 10 to 30 minutes.

3. The clopidogrel bisulfate tablets according to claim 1, characterized in that: Mesoporous silica is synthesized by a template method, with a pore size of 5-15 nm and a specific surface area of ​​500-1000 m2 / g. The modified starch adopts acetylated starch with a substitution degree of 0.1-0.

3. The length of the calcium sulfate whisker is 10-50 μm and the diameter is 0.5-2 μm. In the preparation process of the multi-component composite filler, the mesoporous silica and the modified starch are first mixed and ground in a high-speed ball mill, with a ball-to-material ratio of 5-10:1, a grinding speed of 300-500 rpm, a grinding time of 30-60 minutes, and then the calcium sulfate whisker is added and the mixing is continued for 10-20 minutes.

4. The clopidogrel bisulfate tablets according to claim 1, characterized in that: The hyperbranched polyester-polysaccharide graft is synthesized by free radical polymerization reaction, the branching degree of the hyperbranched polyester is 0.4-0.6, the polysaccharide is gum arabic, and the grafting rate is 20-40%. In the granulation process, the hyperbranched polyester-polysaccharide graft is premixed with other internal auxiliary materials by ultrasonic dispersion, the ultrasonic frequency is 20-40kHz, the ultrasonic time is 5-10 minutes, and then the conventional granulation operation is carried out. The external ion exchange resin complex is composed of a strongly acidic cation exchange resin and a weakly basic anion exchange resin in a mass ratio of 1-2:1, and the ion exchange capacity is 2-5mmol / g. The composite is added by air flow dispersion technology in the total mixing process.

5. The clopidogrel bisulfate tablets according to claim 1, characterized in that: The sodium alginate-chitosan-polyethylene glycol terpolymer is prepared by solution blending and cross-linking reaction. The mass ratio of sodium alginate to chitosan is 1-2:1, the molecular weight of polyethylene glycol is 4000-8000, glutaraldehyde is selected as a cross-linking agent, and the amount used is 0.5-1.5% of the total mass of the terpolymer as an adhesive. Before use, the terpolymer is prepared into an aqueous solution with a concentration of 8-12%, and 0.1-0.3% of sodium dodecyl sulfate is added to the solution as a surfactant. During the granulation process, the adhesive solution is slowly dripped into the material through a peristaltic pump, the dripping speed is 2-5 ml / min, and low-speed stirring is performed at the same time, and the stirring speed is 50-100 rpm.

6. The clopidogrel bisulfate tablets according to claim 1, characterized in that: The graphitized carbon nanotube-zinc stearate composite powder is prepared by an in-situ synthesis method. The graphitized carbon nanotube has a length of 5-20 μm and a diameter of 20-50 nm. Zinc stearate nanoparticles are uniformly loaded on the surface of the graphitized carbon nanotube. During the total mixing process, the composite powder is added three times, and mixed for 3-6 minutes after each addition. The mixer adopts a double cone mixer, and ultrasonic vibration is applied during the mixing process. The ultrasonic power is 30-60 W and the frequency is 30-50 kHz.

7. The clopidogrel bisulfate tablets according to claim 1, characterized in that: The smart responsive polymer is a temperature-pH dual responsive poly (N-isopropylacrylamide-acrylic acid) copolymer, whose lower critical solution temperature is 30-35°C, the antioxidant is natural tocopherol, the ultraviolet absorber is 2-hydroxy-4-methoxybenzophenone, and the biodegradable pigment is sodium copper chlorophyll. In the preparation process of the coating material of the functional coating layer, the smart responsive polymer is first swelled in an ethanol-water mixed solvent, the volume ratio of ethanol to water is 2-4:1, the swelling time is 2-4 hours, and the swelling temperature is 35-45°C, and then the antioxidant, ultraviolet absorber and biodegradable pigment are added in sequence, and stirred under light-proof conditions, the stirring speed is 60-100rpm, and the stirring time is 40-80 minutes to obtain a coating solution. The coating process uses fluidized bed coating equipment with an inlet air temperature of 45-65°C, an outlet air temperature of 35-55°C, a pressure in the coating bed of 0.08-0.12MPa, and a spray rate of 6-10ml / min.

8. The method for preparing clopidogrel bisulfate tablets according to any one of claims 1 to 7, characterized in that: The preparation method is: When preparing the tablet core, firstly, the quantum dot-modified clopidogrel hydrogen sulfate, the multi-component composite filler, the internal disintegrant, and the composite binder solid powder are placed in a planetary ball mill for premixing, the ball mill revolution speed is 100-150rpm, the rotation speed is 200-300rpm, and the premixing time is 5-10 minutes; Then, a wetting agent, purified water, is added for wet granulation. During the granulation process, the stirring speed is 150-250 rpm, the shear speed is 600-1000 rpm, the granulation time is 10-20 minutes, and the wet granules are vacuum freeze-dried. The freezing temperature is minus 30-minus 10°C, the vacuum degree is 0.08-0.15 MPa, and the drying time is 24-48 hours. The dried particles are sized by air flow classification. The dry particles are put into a high-speed mixer for total mixing, and the external disintegrant ion exchange resin complex is first added and mixed for 12-20 minutes, and then the special lubricant graphitized carbon nanotube-zinc stearate composite powder is added and mixed for 6-10 minutes.

9. The method for preparing clopidogrel bisulfate tablets according to claim 8, characterized in that: The mixed granules are tableted by a fully automatic rotary tablet press, with a tableting speed of 200,000-400,000 tablets per hour, a tableting pressure of 70-120 kN, a tablet weight difference controlled within ±2%, and a hardness of 70-100 N. After tableting, the plain tablets were functionally coated. The coated tablets showed specific dissolution behavior in a variety of in vitro dissolution media simulating the environment of different parts of the human gastrointestinal tract. In the simulated gastric environment, the pH was 1.5-2.5, pepsin was contained, the temperature was 37°C, the rotation speed was 50rpm, the cumulative dissolution in 10 minutes was 20-35%, the cumulative dissolution in 30 minutes was 40-60%, and the cumulative dissolution in 60 minutes was 65-85%; In the simulated environment of the anterior small intestine, the pH is 5.5-6.5, containing trypsin, the temperature is 37°C, the rotation speed is 50rpm, the cumulative dissolution in 10 minutes is 30-45%, the cumulative dissolution in 30 minutes is 55-75%, and the cumulative dissolution in 60 minutes is 75-95%; In a simulated environment of the posterior small intestine, with a pH of 7.0-8.0, a temperature of 37°C, and a rotation speed of 50 rpm, the cumulative dissolution in 10 minutes was 40-60%, the cumulative dissolution in 30 minutes was 65-85%, and the cumulative dissolution in 60 minutes was 85-100%.

Citation Information

Cited By

  • Preparation process of midodrine hydrochloride solid preparation and midodrine hydrochloride solid preparation

    CN120661456A